PENGARUH MANAJEMEN SARANA DAN PRASARANA TERHADAP PEMBELAJARAN DI TK KECAMATAN MATARAM KOTA MATARAM - Sakinah Dwi Handayani; Abdul Kadir Jaelani; Ika Rachmayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of facilities and infrastructure management on children's learning in Kindergarten, Mataram District, Mataram City. This research mode uses quantitative by using a quantitative descriptive research type. The data subjects in this study were 31 heads of kindergartens/institutions in Mataram District, Mataram City. The data collection technique uses questionnaire and documentation methods. The data analysis techniques used were validity test, reliability test and hypothesis test. The results of the simple linear regression analysis obtained a value of R = 0.967 with R Square = 0.935, which means that 93.5% of the variation in children's learning can be explained by the management of facilities and infrastructure, while the remaining 6.5% is influenced by other factors outside the study. The F-value of the calculation = 257.393 with a significance of 0.000 (< 0.05) confirms that the regression model is statistically significant. In addition, the t-test showed that the variable of facilities and infrastructure management had a t-count = 16.043 with a significance value of 0.000 (< 0.05), meaning that Ha was accepted and Ho was rejected. So it is concluded that the management of facilities and infrastructure can affect the learning of kindergarten children in Mataram District, Mataram City.